Konseling Individu: Implementasinya dalam Mengatasi Masalah Penyesuaian Diri Santri Baru - Ahmad Fasya Alfayadl (Institut Agama Islam Negeri Curup, 2022)
This article discusses someone who enters his early teens experiencing problems in his self-concept, this is caused by personal or environmental reasons. Therefore, it is not uncommon for them to withdraw from the new environment, as happened in Islamic boarding schools. Not a few new students at junior high school age who enter Islamic boarding schools experience difficulties in adjusting themselves. The purpose of this research is to help new students overcome adjustment problems in their new environment, as well as provide an understanding regarding adjustment. Counselors help overcome the problems faced by these new students by providing individual counseling services using a client centered approach. The counseling stages carried out by the assessment, the work stage, and the evaluation. Therefore, the research method used is descriptive qualitative, because the approach used is a case study. Data collection techniques used are interviews and observation. The conclusion obtained is that new students need an introduction to their new environment, as well as being given motivation and assistance so they don't withdraw from their environment.